Nucleic acids through condensation of nucleosides and phosphorous acid in the presence of sulfur - Lönnberg, Tuomas (Beilstein J Org Chem, 2016)
Short phosphorothioate oligonucleotides have been prepared by refluxing an equimolar mixture of thymidine and triethylammonium phosphite in toluene in the presence of elemental sulfur. Desulfurization and subsequent digestion of the products by P1 nuclease revealed that nearly 80% of the internucleosidic linkages thus formed were of the canonical 3´,5´-type.